Eco product innovation in search of meaning: incremental and radical practice for sustainability development - Lizwa, Rashid; Salleh, Yahya; Samer Ali, Shamee; Juhaini, Jabar; Muliati, Sedek; Sarah, Halim (CCSE, 2014)
Purpose: The purpose of this paper is to discuss the role of eco innovation in order to achieve sustainable development in manufacturing industries. The outcomes of this paper attempts to describe the main drivers of eco innovation among companies, core categories of eco innovation practices in manufacturing industry and framework of radical and incremental eco product innovation. The last part of the paper provides the insight of the new paradigm for eco innovation research in new millennium particularly in developing countries.